2011
DOI: 10.1016/s0929-6646(11)60055-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type 2 Diabetes Mellitus on the Clinical Severity and Treatment Outcome in Patients With Pulmonary Tuberculosis: A Potential Role in the Emergence of Multidrug-resistance

Abstract: DMTB patients have more severe TB infections, which require longer treatment and are more likely to develop MDR-TB than are patients with TB alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
111
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 24 publications
17
111
3
3
Order By: Relevance
“…This result is comparable to the result reported in Fiji [31], in Ethiopia [32] and those reported by Kelly Dooley in 2009 [33] but different from the reported study in China [34] in Texas-Mexico [35], Taiwan [36], Maharashtra-India [37], Saudi Arabia [38], and Turkey [39] where sputum conversion among TBDM patient groups were lower. The good sputum conversions observed in both patient groups in our study may be related to good treatment adherence among patients.…”
Section: Discussionsupporting
confidence: 75%
“…This result is comparable to the result reported in Fiji [31], in Ethiopia [32] and those reported by Kelly Dooley in 2009 [33] but different from the reported study in China [34] in Texas-Mexico [35], Taiwan [36], Maharashtra-India [37], Saudi Arabia [38], and Turkey [39] where sputum conversion among TBDM patient groups were lower. The good sputum conversions observed in both patient groups in our study may be related to good treatment adherence among patients.…”
Section: Discussionsupporting
confidence: 75%
“…For example Chang et al reported a delayed clearance of mycobacteria in patients with TB + DM when compared with TB patients without DM (2.5 ± 3.0 months vs. 1.6 ± 1.4 months, p < 0.01) [2].…”
Section: Discussionmentioning
confidence: 99%
“…The bacteriological conversion has been reported to be slower in patients with DM in comparison to that of non-diabetic patients in some reports [2][3][4], and uncontrolled DM (HbA1c ≥ 7) has been reported as a significant risk factor for positive sputum culture after two months [5]. Other reports, however, do not show DM to be an independent risk factor associated with increased time to sputum conversion [6] or any relation between DM and sputum conversion rate at the end of the 2nd month [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…20 With regard to the rate of positive smears at the time of diagnosis, results are conflicting. Although, some authors reported a higher frequency of negative sputum smears among TB-DM cases, 26 others found DM as an independent risk factor for numerous acid-fast bacilli on the sputum smear examination 24 and some showed no association between DM and patient's bacteriology results. Conflicting results might be due to the control status of DM.…”
Section: Sputummentioning
confidence: 96%
“…20 A few other studies have shown that the clinical characteristics of TB do not differ among diabetic and non-diabetic patients. [24][25] In our study, all of the patients (100%) were presented with cough as a common symptom with mean A1c of 8.47 ± 0.03 followed by fever (94.6%) with mean A1c of 8.44 ± 0.05, breathlessness (73.4%) with mean A1c of 8.51 ± 0.12, loss of appetite (68%) with mean A1c of 8.18 ± 0.04, weight loss (24.4%) with mean A1c of 8.55 ±0.06 and hemoptysis (26.5%) with mean A1c of 9.12 ±0.23. There is no correlation of mean A1c level with symptomatology.…”
Section: Sputummentioning
confidence: 99%